Sobre la ontología inmaterialista: el concepto de idea en Berkeley - López, Alberto Luis (2019)
“On Immaterialist Ontology: The Concept of Idea in Berkeley”. Berkeley’s immaterialist philosophy has been frequently underestimated as a result of the misunderstanding of his ontological proposal, specifically because of the complexity of his concept of idea. The aim of this paper is then to clarify and explain that concept because from it depends the correct understanding of Berkeley’s ontological and immaterialist proposal. To do this, 1) I will show some examples of the misunderstanding that the berkeleian proposal has had, mainly due to his concept of idea; 2) I will track how this notion was being developed in Berkeley’s early notes, known as Philosophical Commentaries; 3) I will analyze and explain the concept of idea from the published work of Berkeley, that is, from the Principles and Dialogues.